Transformasi Wakaf Konsumtif ke Wakaf Produktif: Studi Fikih Akad dan Tantangan Implementasi Kontemporer: Transformation of Consumptive Waqf into Productive Waqf: A Study of Fiqh of Contracts and Contemporary Implementation Challenges - Farida Aprianti; Andi Amma Ruhmah; Hamzah Haeriyah; Abdi Wijaya; Muhammad Rusdin (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2026)
This study examines the transformation of consumptive waqf into productive waqf through the lens of fiqh contracts and contemporary governance challenges. The urgency of the study arises from the paradox between Indonesia’s large waqf assets and the limited productive utilization of those assets. Official data reported in 2024 show that Indonesia has hundreds of thousands of waqf land locations, while only a small proportion is optimally utilized for productive purposes. This study employs qualitative library research with normative-juridical and conceptual approaches. Data were obtained from classical fiqh literature, statutory regulations, fatwas, recent reputable journal articles, and official reports from waqf authorities. The findings indicate that the transformation of waqf is not a deviation from the principle of perpetuity, provided that the substance of tahbis al-ashl and tasbil al-manfa’ah is preserved. The reconstruction of contracts can be carried out through controlled istibdal, long-term ijarah, mudharabah, musyarakah mutanaqisah, wakalah bi al-istitsmar, and Build-Operate-Transfer schemes, depending on asset characteristics and risk profiles. The main contemporary challenges consist of legal-administrative fragmentation, limited nazhir competence, low public literacy, financing constraints, weak accounting transparency, and insufficient integration between waqf assets and the halal industry value chain. The novelty of this study lies in proposing a layered contract reconstruction model that integrates fiqh legitimacy, governance safeguards, digital accountability, and halal industry orientation. The study recommends strengthening nazhir certification, standardizing contract-based risk mitigation, and developing an integrated digital reporting system for productive waqf.